Hubungan Antara Harga Diri Dengan KecenderunganPerilaku Bullying Pada Siswa Smp - Eny Rahmawati, Fitriyana (2016)
ABSTRACTION Adolescence is a very dynamics period of life. It is the period of very rapid developments and changes. This period is a transition period, and teens tend to have a high risk of occurrence of delinquency and violence both as victim and as perpetrator of violence, especially that lead to bullying behavior tendencies. One factor that influences predisposition of bullying behavior is self-esteem. Selfesteem is part of the basic human needs such as self-esteem needs which include the respect from the family and society, as well as a feeling of respect for others. high self-esteem individuals are usually more able to survive and adapt to the needs and pressures better than having low self esteem. The research objectives are: to know whether there is a relationship between self-esteem with a tendency to bullying behavior. The hypothesis proposed is that there is a negative relationship between self-esteem with a tendency to bullying behavior. The subjects in this study are seventy students, while the populations in this study are all students of SMPN 16 Surakarta. Data collection instrument in this research uses the scale of self-esteem and bullying behavior tendencies. The data analysis technique uses moment product correlation. The analysis results obtained from this research that there is a very significant negative correlation between self-esteem with a tendency to bullying behavior. Self esteem contributes 11.1% and determinant coefficient (r ) 0.111 in influencing the bullying behavior tendency. The self-esteem level is high, while the level of bullying behavior tendency is low. Keywords: Self-esteem, Bullying behavior tendency.